2002
DOI: 10.1242/jeb.205.19.3039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ion transport inPotamotrygon, a stenohaline freshwater elasmobranch native to the ion-poor blackwaters of the Rio Negro

Abstract: SUMMARYStingrays of the family Potamotrygonidae are the only stenohaline freshwater elasmobranchs. Potomotrygon sp. collected from the ion-poor blackwaters ([Na+], [Cl-] and[Ca2+]=10-30 μmol l-1, pH 6.1) of the Rio Negro,Amazonas, Brazil, were ammoniotelic (91% ammonia-N, 9% urea-N excretion) and exhibited blood chemistry (Na+, Cl-, urea, ammonia and glucose levels and osmolality) typical of freshwater teleosts. Unidirectional Na+ and Cl- influx rates, measured with radiotracers,displayed saturation kinetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(5 citation statements)
references
References 78 publications
(131 reference statements)
1
4
0
Order By: Relevance
“…However, sodium levels were similar with Potamotrygon spp. (164 ± 5.6 mmol.L -1 ), P. magdalenae (141 ± 2.4 mmol.L -1 ) and Potamotrygon sp (178,2 ± 4.8 mmol.L -1 ) (WOOD et al, 2002;CAIN;HARMS;SEGARS, 2004;ROBINSON, 2010). Chlorine and potassium was also similar with P. magdalenae (147 ± 4.5 and 8,5 ± 0.29 mmol.L -1 ) (OGAWA; HIRANO, 1982), but calcium level was higher (3 ± 0.09 mg.dL -1 ).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, sodium levels were similar with Potamotrygon spp. (164 ± 5.6 mmol.L -1 ), P. magdalenae (141 ± 2.4 mmol.L -1 ) and Potamotrygon sp (178,2 ± 4.8 mmol.L -1 ) (WOOD et al, 2002;CAIN;HARMS;SEGARS, 2004;ROBINSON, 2010). Chlorine and potassium was also similar with P. magdalenae (147 ± 4.5 and 8,5 ± 0.29 mmol.L -1 ) (OGAWA; HIRANO, 1982), but calcium level was higher (3 ± 0.09 mg.dL -1 ).…”
Section: Discussionsupporting
confidence: 59%
“…The absence of eosinophils in P. scobina could be physiological, as well as in teleost fish generally there is great variation in their blood percentage (TAVARES-DIAS; MORAES, 2004). Wood et al (2002) showed that Potamotrygonidae family presents characteristics of both freshwater and marine fish, based on the study of sodium and chloride exchange and urea excretion in Potamotrygon hystrix and Potamotrygon thorsoni. Emery (1986) associated the low metabolic activity of these fish with the low rates of ion exchanges in this family, which was also observed in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the work present in the literature with freshwater stingrays in natural environments was carried out mainly in black water environments in the Negro River basin, Amazonas (Brito et Wood et al 2002), and to date, there are no studies on the determination of hematological reference intervals for stingrays from white water environments in the Amazon hydrographic basin.…”
Section: Introductionmentioning
confidence: 99%
“…Campbell et al ., (1997) demonstrated, by transmission electron microscopy, that DOC molecules can bind directly to the surface of gill cells. In fish exposed to acidic waters, DOC mitigates the inhibition of Na + uptake and ammonia excretion (Wood et al , 2003; Al-Reasi et al , 2016;), lowers the transepithelial potential (TEP) (Galvez et al , 2008), protects against the elevation of diffusive Na + and Cl − loss (Wood et al , 2002, 2003; Gonzalez et al , 2002, 2006; Al-Reasi et al , 2016; Duarte et al , 2016, 2018) and reduces the gill binding and toxicity of metals (Wood et al ., 2011; Cremazy et al ., 2016; Duarte et al ., 2021). Humic DOC has also been shown to significantly decrease respiratory stress caused by exposure to low pH and increase survival of fish at pH 4 (Holland et al ., 2014b).…”
Section: Introductionmentioning
confidence: 99%